Pharmacogenomics Tools for Precision Public Health and Lessons for Low- and Middle-Income Countries: A Scoping Review - Borbón A; Briceño JC; Valderrama-Aguirre A (Pharmacogenomics and Personalized Medicine)
Angélica Borbón,1 Juan Carlos Briceño,2 Augusto Valderrama-Aguirre3 1Technological Innovation Management, University of the Andes, Bogotá, Colombia; 2Department of Biomedical Engineering, Director of Technological Innovation Management Programs, University of the Andes, Bogotá, Colombia; 3Department of Biological Sciences, Faculty of Sciences, Director of the Biomedical Research Institute Group, University of the Andes, Bogotá, ColombiaCorrespondence: Augusto Valderrama-Aguirre, Email a.valderramaa@uniandes.edu.coAbstract: Pharmacogenomics is the integration of genomics and pharmacology to optimize drug response and reduce side effects. In terms of personalized or individualized medicine, PGx is defined as the identification and analysis of specific genetic variants associated with particular drug treatments for each patient. Under a precision public health (PPH) approach, population-level data are analyzed to generate public health strategies. The objective of this study was to conduct a scoping review of technological tools, examining their evolution, the predominance of high-income countries in their development, and the gaps and needs for genomic data and advances in low- and middle-income countries (LMICs). This review was conducted in accordance with the ScPRISMA guidelines. A search was conducted in PubMed, Web of Science and Embase until January 2024. A total of 40 documents were selected, which revealed the continuous evolution and progressive development of pharmacogenomic tools. The technological tools developed come from high-income countries, particularly the United States, Canada, China, and several European nations, where international collaboration has been essential to maintain and expand these tools, which have evolved to keep pace with the rapid generation of genomic data. This trend shows a scarce development of technological tools for public health precision in LMICs, which evidences the need to increase investment in genomic research infrastructure in this aspect and in the development of capacities to guarantee global accessibility and boost PPH for all populations.Keywords: personalized medicine, pharmacogenomics, precision public health, technological tools